2019
DOI: 10.1002/pat.4620
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing of fire‐retardant ethylene‐vinyl acetate

Abstract: Thermocompression (with also extrusion and injection molding) is a classical polymer shaping manufacturing, but it does not easily allow designing sophisticated shapes without using a complex mold, on the contrary to 3D printing (or polymer additive manufacturing), which is a very flexible technique. Among all 3D printing techniques, fused deposition modeling is of high potential for product manufacturing, with the capability to compete with conventional polymer processing techniques. This is a quite low cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
(25 reference statements)
1
25
0
1
Order By: Relevance
“…As will be shown in Section 4, many new experimental systems for both small- and large-scale applications appeared in the period from 2014 to 2018 [ 15 – 29 , 32 , 34 , 35 , 37 ], which can be related to the high number of publications in the same period. Although the scientific production in the last 2 years decreased, a crescent share of the research was carried out with commercial systems [ 48 , 49 , 51 , 53 , 54 , 65 – 69 , 71 73 , 75 ], indicating the consolidation of screw-assisted EAM in the market.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As will be shown in Section 4, many new experimental systems for both small- and large-scale applications appeared in the period from 2014 to 2018 [ 15 – 29 , 32 , 34 , 35 , 37 ], which can be related to the high number of publications in the same period. Although the scientific production in the last 2 years decreased, a crescent share of the research was carried out with commercial systems [ 48 , 49 , 51 , 53 , 54 , 65 – 69 , 71 73 , 75 ], indicating the consolidation of screw-assisted EAM in the market.…”
Section: Search Resultsmentioning
confidence: 99%
“…Although the first systems were mostly used in bio-AM applications [ 11 , 14 ], the concept was further developed from 2014 to 2019 to different purposes [ 17 , 18 , 37 , 39 , 40 ]. An expressive equipment variety for small-scale applications could be observed in the period, including four commercial systems (3D Discovery® [ 45 , 46 ], PAM® [ 51 ], M3DIMAKER® [ 53 ], ExAM 255® [ 54 ]). Despite the description of the first screw-assisted EAM based on a do-it-yourself (DIY) printhead kit [ 41 ], no significant equipment improvements were introduced in 2020.…”
Section: Technological Evolution Of Screw-assisted Eammentioning
confidence: 99%
“…A critical amount of ATH is desirable to generate an effective homogenous residue, which acts as a fire barrier layer. This barrier formation was not accomplished at low ATH concentration (i.e., 30 56) to accomplish light-weight 3D-printed parts with better flame retardancy. The design contains a core part, which was covered with an outer shell part.…”
Section: Ethylene-vinyl Acetate (Eva)mentioning
confidence: 99%
“…EVA/ATH (30 wt.%) pellets were then used to print 50x50x3 mm 3 EVA/ATH (30 wt.-%) polymer plates, according to a computer pattern using a Pollen (Ivry-sur-Seine, France) 3D printer, fully described elsewhere [7]. EVA/ATH (30 wt.-%) polymer pellets were incorporated on a feeder, then went through an extruder with a thermal gradient from 65°C to 130°C in the middle until 225°C at the output of extruder.…”
Section: Printed Samplesmentioning
confidence: 99%
“…In a previous paper, it was reported that a fire-retarded formulation of an ethylene-vinyl acetate (hereafter call EVA) copolymer containing 30% weight amount of Aluminum TriHydroxide (ATH) can be processed to create flame-retardant materials by 3D-printing [7]. Following this research, an original design was elaborated and innovative sandwich multimaterials filled with a liquid phase were prepared.…”
Section: Introductionmentioning
confidence: 99%